Unraveling the neurological enigma: central diabetes insipidus and extrapontine osmotic demyelination caused by covid-19 case report: Desentrañando el enigma neurológico: Diabetes insípida central y desmielinización osmótica extrapontina causada por covid-19-reporte de caso - Aguirre-Flórez, Mateo (2024)
Background: COVID-19 infection produces various symptoms and affects multiple systems, including the endocrine system. Lesions have been documented at the hypothalamic and pituitary axis, hypothetically explained by the presence of angiotensin II receptors in these structures and by direct immune-mediated viral lesions. These manifest with electrolyte and hormonal alterations. Case report: We present the case of a female patient who, after infection by SARS-CoV-2, presented with hypernatremia refractory to conventional management. Her diagnostic study documented hyposthenuria, high serum osmolarity, and low urinary osmolarity. The condition was corrected with desmopressin, leading to a diagnosis of central diabetes insipidus. A brain MRI revealed a lesion in the pituitary gland, confirming the clinical findings. The only etiological hypothesis for this lesion is its association with SARS-CoV-2 infection. Conclusions: Understanding the complications secondary to COVID-19 infection in the endocrine setting is essential for early diagnosis and targeted treatment. This knowledge can significantly improve the quality of life for patients affected by such complications.